Creating an e-portfolio application for the development of educational leaders - Dixon, Robert (Australian Association for Research in Education, 2011)
This paper is a result of a study which followed the development of aspiring and current school leaders as they negotiated an e-portfolio application created by the author. The portfolio aimed to promote reflective practice, professionalism and accountability in users. The following outlines the authoring of the portfolio software and reports on the perceptions of users as to its efficacy during a one year trial period. It outlines in detail the architecture of the portfolio and the engineering of the application. The portfolio design, which was influenced by Quintana, Reiser, Davis, Krajcik, Golan, Kyza, Edelson and Soloway (2002) underpins concerns in terms of cognitive considerations for scaffolding the process management, sense making and articulation issues in software construction. The features and stages of implementation are provided and an overview of the conceptualisation and design of the portfolio is described. Access and navigation details are detailed and illustrated. Examples of how participants in the project negotiated the portfolio and inserted artefacts to demonstrate leadership qualities and characteristics are discussed. The study found that designing an e-portfolio which provides for the growth of educational leadership requires careful preparation in terms of design elements such as planning and goal setting, the development of collaboration between participants, linking capabilities, flexibility of application, transportability, start up costs and maintenance. It needs a foundation of a well researched conceptual framework, (in this case the Wildy & Louden, 2002 Leadership Framework), thoughtful implementation and training and it needs to be easy to use. Participants were positive about the impact of the portfolio on their capacity for the creation of a vision which transformative leaders aspire to. Creating a portfolio had the additional effect of a growing perception of improved ICT skills by participants. The study concludes that an e-portfolio such as described in this paper, has the potential to be a powerful tool for developing educational leadership skills